Enzymatic Cellulose Palmitate Synthesis Using Immobilized Lipase - Anna Roosdiana; Diah Mardiana; Ellya Indahyanti; Dyah Ayu Oktavianie (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2017)
Bacterial cellulose can be modified by esterification using palmitic acid and Mucor miehei lipase as catalyst. The purpose of this research was to determine the optimum conditions of esterification reaction of cellulose and palmitic acid . The esterification reaction was carried out at the time variation of 6, 12, 18, 24 and 30 hours and the mass ratio of cellulose: palmitic acid (1: 11: 2, 1: 3, 1: 4, 1: 5,1:6) at 50 °C. The cellulose palmitate was examined its physical and chemical properties by using FTIR spectrophotometer, XRD, bubble point test and saponification apparatus. The results showed that the optimum reaction time of esterification reaction of cellulose and palmitic acid occurred within 24 hours and the mass ratio of cellulose: palmitic acid was 1: 3 resulting in DS of 0.376 with swelling index of 187 %, crystallinity index of 61.95%, and Φ porous of 2.40 μm. Identification of functional groups using FTIR spectrophotometer showed that C=O ester group was observed at 1737.74 cm-1 and strengthened by the appearance of C-O ester peak at 1280 cm-1. The conclusion of this study is reaction time and reactant ratio influence significantly the DS of cellulose ester.